An exploratory study of organizational culture and the personal experiences of TEFL instructors in Chinese - ZHANG XIAOMENG, ZHANG XIAOMENG; DR. NIDHI AGARWAL, DR. NIDHI AGARWAL (International Journal of Multidisciplinary Research and Studies, 2024)
There are four areas in which this study will help improve education in China. Students' success is proportional to their teachers' enthusiasm, which in turn affects students' sense of competence, pride, and optimism about their own educational futures (Day, 2005). Teachers have a deep understanding of their subjects, and they foster an environment where students feel comfortable asking questions and contributing to class discussions (Day, 2005). Dinham and Scott's (1996) research on teacher happiness, motivation, and health found that two major sources of satisfaction were the success of their students and their own professional development. Student motivation, teacher motivation, curriculum design, and curriculum implementation were all determined to have a high degree of association by Atkinson (2010). Language teachers, according to Bernaus and Gardner (2008), can use motivating strategies to boost their students' skill development, classroom cooperation, and overall atmosphere. It has been shown via studies such as the one done by Filak and Sheldon in 2008 that the level of autonomy granted to teachers has a direct impact on student motivation. The study is an empirical investigation of a well-known but under-researched phenomenon: the lack of intrinsic desire among Chinese academics to educate (Lu, 2004). The purpose of this study is to contribute new data to the growing body of literature on the subject of lecturer motivation in China. As a third reason for the study's significance, educational administration must implement regulations that provide the most conducive environment for work. The energy and interest of teachers are vital to a successful classroom. These results might inform policymakers in China on the question of whether or not academics should have more autonomy in their professional lives. Since the study's driving theory, Self-Determination Theory (SDT), will be implemented in a cultural context distinct from the one in which it was first conceived, it also has theoretical value. It was developed in the United States and has had widespread application in studies of cultural differences (Chirkov, Ryan, & Willness, 2005; Deci, Ryan, Gagne, Leone, Usunov, & Kornazheva, 2001). However, the cultural assumptions behind the theory aren't necessarily applicable to the situation in China. Buddhism, which has been widely practiced in China for over a thousand years, and Confucianism, which was introduced to China from India during the Tang Dynasty, are two examples of the tacit principles that have had a profound effect on Chinese history and culture (Lu, 2001). To create their own unique perspectives on life and work, contemporary Chinese culture has merged the three major philosophical traditions with Western ideas. Since this study focused on the cultural features of SDT, we now have a better grasp on them.